Brain morphological analysis in mice with hyperactivation of the hedgehog signaling pathway - Shiohama, Tadashi; Uchikawa, Hideki; Nitta, Nobuhiro; Takatani, Tomozumi; Matsuda, Shingo; Ortug, Alpen; Takahashi, Emi; Sawada, Daisuke; Shimizu, Eiji; Fujii, Katsunori; Aoki, Ichio; Hamada, Hiromichi (Frontiers in Neuroscience, 2024)
Hedgehog signaling is a highly conserved pathway that plays pivotal roles in morphogenesis, tumorigenesis, osteogenesis, and wound healing. Previous investigations in patients with Gorlin syndrome found low harm avoidance traits, and increased volumes in the cerebrum, cerebellum, and cerebral ventricles, suggesting the association between brain morphology and the constitutive hyperactivation of hedgehog signaling, while the changes of regional brain volumes in upregulated hedgehog signaling pathway remains unclear so far. Herein, we investigated comprehensive brain regional volumes using quantitative structural brain MRI, and identified increased volumes of amygdala, striatum, and pallidum on the global segmentation, and increased volumes of the lateral and medial parts of the central nucleus of the amygdala on the detail segmentation in Ptch heterozygous deletion mice. Our data may enhance comprehension of the association between brain morphogenic changes and hyperactivity in hedgehog signaling.